A triad of cluster-like headaches with delayed development of a macroscopic prolactinoma: A case report. (5th March 2020) - Ihezie, Stephanie A; Chandalia, Manisha; Burish, Mark J
Pituitary hormone testing is recommended in refractory cluster headache (CH), but supporting evidence is limited. We present a patient with cluster-like headaches and a negative brain magnetic resonance imaging (MRI) 1 year after headache onset. He failed multiple medication trials. Three years after headache onset, additional workup showed abnormal pituitary labs including hyperprolactinemia and a brain MRI with a 15 × 15 × 14 mm 3 enhancing pituitary lesion. With cabergoline 0.25 mg twice weekly, the patient has been headache-free for over 2 years. This case supports the recommendations for pituitary testing in refractory CH, even if imaging is initially negative for a pituitary tumor.